The Effect of Grandchildren on Grandparental Labour Supply: Evidence from Europe - Andreas Backhaus; Mikkel Barslund (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Grandparents at working-age spend a considerable amount of time taking care of their grandchildren. These time transfers might imply economic trade-offs regarding the participation in the labour market. Using an instrumental variable strategy and multiple waves of the Survey of Health, Ageing and Retirement in Europe (SHARE), we estimate the causal effect of grandparenthood on the labour supply of working-age grandparents in ten European countries. In our preferred specification, we find a large negative impact of grandparenthood on the labour supply of women aged 55 to 64. This effect is particularly pronounced following the arrival of the first grandchild and for grandmothers who live in close distance to their offspring. It further operates at the extensive margin of labour supply, resulting in grandmothers leaving the labour market entirely. By contrast, male labour supply does not significantly adjust in response to grandparenthood. Our results imply a relevant trade-off between labour supply and grandchild care for European women of later working age.
Keywords: 330